2017
DOI: 10.1097/aco.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced peripheral neuropathy

Abstract: Despite the volume of recent publications, there are limited preventive or therapeutic strategies for CIPN supported by high-level evidence. Duloxetine remains the only pharmacologic agent with demonstrated benefit; its clinical use should be routinely considered. Moving forward, nonopioid analgesic therapies will likely play an increasing role in CIPN treatment, but further research is necessary to confirm their utility. Promising therapies include vitamin B12 supplementation, physical therapy, and various fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 68 publications
0
10
1
2
Order By: Relevance
“…Neurological toxicity has been a commonly reported DLT during the clinical development of tubulin-binding agents and could not be effectively prevented or treated [22][23][24][25]. Similar recoverable peripheral sensorimotor neuropathy in this trial was observed when 65 mg/m 2 CA4P was administered to Chinese patients with grade 2 lower extremity weakness [21]. These were not seen in western patients.…”
Section: Study Completedmentioning
confidence: 51%
See 2 more Smart Citations
“…Neurological toxicity has been a commonly reported DLT during the clinical development of tubulin-binding agents and could not be effectively prevented or treated [22][23][24][25]. Similar recoverable peripheral sensorimotor neuropathy in this trial was observed when 65 mg/m 2 CA4P was administered to Chinese patients with grade 2 lower extremity weakness [21]. These were not seen in western patients.…”
Section: Study Completedmentioning
confidence: 51%
“…AEs and efficacies observed in this study were similar to those reported for VDAs (Table 4). The partial response in one patient with buccal cancer was consistent with the activity of combretastatin A-4 phosphate (CA4P) in Chinese patients with refractory nasopharyngeal carcinoma [21]. Neurological toxicity has been a commonly reported DLT during the clinical development of tubulin-binding agents and could not be effectively prevented or treated [22][23][24][25].…”
Section: Study Completedmentioning
confidence: 64%
See 1 more Smart Citation
“…Adverse events frequently lead to a reduction of chemotherapy dosage or even to discontinuation of therapy. Clinical effects of analgesics in this population are small [7].…”
Section: Discussionmentioning
confidence: 87%
“…Niestety, nie dysponujemy wiarygodnymi, potwierdzonymi naukowo metodami leczenia w przypadku stwierdzenia objawów polineuropatii obwodowej. Jedynym lekiem, którego działanie zostało udowodnione jest duloxetyna [22]. Obiecujące wydają się rezultaty suplementacji witaminy B12, fizykoterapii czy różnych form neuromodulacji-wymagają jednak potwierdzenia w dalszych badaniach.…”
Section: Neurotoksycznośćunclassified